Uji Akurasi Perhitungan Waktu Ashar menggunakan Rubu’ Al-Mujayyab - Muhammad Hidayat; Arwin Juli Rakhmadi; Hariyadi Putraga (DIKTUM: Jurnal Syariah dan Hukum, 2022)
The study aims to measure the calculation of time using Rubu Al-Mujayyab, in addition to explaining in detail the steps on calculating time of Ashr using Rubu' Al-Mujayyab. The research method used in this research is experimental. The results of this study indicates that Rubu Al-Mujayyab has a fairly high time calculation accuracy, especially in calculating of the Ashr time. It is evident that there is no difference in the results of time calculations using Rubu' Al-Mujayyab by applying the Contemporary Hisab Method and Accurate Times Software. In addition, Rubu Al-Mujayyab can determine the declination of the Sun and there are other functions of the Asr line that can make it easier for users to determine after the beginning of time until the length of the shadow of an object is doubled or the beginning of time.